The Essence of Multiculture for Students through Module in Faculty of Education, Medan State University - Nur'aini Nur'aini (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
The learning process has not been optimal in the multicultural counseling course. There are many ways that lecturers can do so that the learning process can be optimal, one of which is by using learning media such as modules. This study aims to develop a multicultural counseling course module and describe the feasibility level of the module by experts and students. This research is a development using a model namely Define, Design, Develop, Disseminate. The subject of the research product validity test involved two material experts and two media experts and the product quality testing was carried out on 40academic year2018 students Guidance and Counseling Study Program Faculty of Education, State University of Medan. Data analysis techniques for product feasibility use quantitative descriptive analysis. The results showed (1) a developed multicultural counseling course module was available, (2) a multicultural counseling module was assessed as feasible by material experts, obtained a percentage of 80.36% and a media expert obtained 77.50% and a module quality test by students obtained at 87.20% with very decent category. This result is in the feasible category and the product can be used by lecturers and students in the learning process, especially in the multicultural counseling subject.